A qualitative exploration of the collaborative working between palliative care and geriatric medicine: Barriers and facilitators from a European perspective. Issue 1 (December 2016) - Albers, Gwenda; Froggatt, K.; Van den Block, L.; Gambassi, G.; Vanden Berghe, P.; Pautex, S.; Van Den Noortgate, N.
Abstract Background With an increasing number of people dying in old age, collaboration between palliative care and geriatric medicine is increasingly being advocated in order to promote better health and health care for the increasing number of older people. The aim of this study is to identify barriers and facilitators and good practice examples of collaboration and integration between palliative care and geriatric medicine from a European perspective. Methods Four semi-structured group interviews were undertaken with 32 participants from 18 countries worldwide. Participants were both clinicians (geriatricians, GPs, palliative care specialists) and academic researchers. The interviews were transcribed and independent analyses performed by two researchers who then reached consensus. Results Limited knowledge and understanding of what the other discipline offers, a lack of common practice and a lack of communication between disciplines and settings were considered as barriers for collaboration between palliative care and geriatric medicine. Multidisciplinary team working, integration, strong leadership and recognition of both disciplines as specialties were considered as facilitators of collaborative working. Whilst there are instances of close clinical working between disciplines, examples of strategic collaboration in education and policy were more limited. Conclusions Improving knowledge about its principles and acquainting basic palliative care skills appears mandatory for geriatricians and other health care professionals. In addition, establishing more academic chairs is seen as a priority in order to develop more education and development at the intersection of palliative care and geriatric medicine.